Billedstenen fra Snaptun - Gestsson, Gisli (Kuml, 1961)
Snaptun On the forge-stone found on the beach by Snaptun in Horsens Fjord, a man’s head is depicted whose lips bear traces of having been sewn together (P. V. Glob in KUML 1959). A reference in Skaldskaparmál in Snorri Sturluson’s Edda leads to the supposition that the man’s head must represent Loki. This god had waged his head against the dwarf, Brokk’s, if the latter’s brother, Sindri, succeeded in making three treasures finer than those he himself had had made, the golden hair, a gift to Sif, his ship, Skidbladnir and Odin’s spear, Gungnir. Sindri set Brokk to mind the bellows of the forge and produced a wild boar with golden bristles, the magic ring, Drypnir and Thor’s hammer. The three treasures won the approval of the gods and Loki lost the wager. When the dwarfs were about to cut off his head, Loki pointed out that they had no right to his neck. So, instead, the dwarfs sewed his lips together. But Loki pulled the stitches out again. The author reminds us that later popular Northern superstition has accorded Loki the role of a fire-being or "vætte" dwelling in the fire of the hearth. It was in harmony with his character that the dwarfs elected to sew Loki’s lips together for he was known for his quarrelsome disposition and ability to get the last word and that he could only be silenced by force. To give vent to his wit he was obliged to tear the stitches out. The man who has carved Loki’s face on the forge-stone from Snaptun has been acquainted with both these qualities of Loki’s. That is why he placed the picture of the glib and spiteful god in the very fire of the smith’s forge. Gisli Gestsson.